Method for Management of Perianal Fistula with New Device: Progressive Curettage of the Tract and Sealing with Platelet-Rich Fibrin - Francisco Javier Perez Lara (Shiraz University of Medical Sciences, 2016)
Surgical treatment of high perianal fistulas, which affect a significant proportion of the sphincter apparatus, is difficult and associatedwith considerable risk of impaired anal continence. The diversity of approaches proposed for the treatment of complexperianal fistulas reflects the fact that no method has yet been shown to be fully satisfactory. We believe the successful treatmentof this condition is directly proportional to the amount of fibrous tissue that can be removed. We used a kit of small curettes, ofdifferent thicknesses and sizes, incorporating spicules that enable the physician to remove fibrous tissue from the fistula tract. Thesmall size and varying thicknesses of the curettes enable them to mold to the curves of the fistula tract and to remove tissue byde-roofing from the shallowest to the deepest layers, thus excising the entire fibrous tract. The tract is then sealed using autologousfibrin, applied through a catheter, with the help of a monitor indicating the amount of product remaining at all times. Finally, theinternal orifice is closed by simple suturing.